2016
DOI: 10.4103/1658-354x.179118
|View full text |Cite
|
Sign up to set email alerts
|

C-MAC® video laryngoscope with D-BLADE™ and Frova introducer for awake intubation in a patient with parapharyngeal mass

Abstract: Parapharyngeal tumors are rare head and neck tumors which can present as an intraoral mass and can pose great challenge to anesthesiologists. The primary concern is the difficult airway due to gross anatomical distortion of the upper airway. Securing the airway in an awake state should be the primary goal of anesthesiologists to avoid catastrophic complications. Herewith, we report the successful use of C-MAC® video laryngoscope with the acute-angle D-BLADE™ in combination with Frova introducer for awake intub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
3
Order By: Relevance
“…We have demonstrated that establishing a fixed protocol that employs videolaryngoscopy and a bougie for tracheal intubation can increase success rates in a HEMS setting. Previous literature includes case series of the use of this method for patients with difficult airway . Traditionally, both devices are used separately and generally only in the case of a difficult airway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that establishing a fixed protocol that employs videolaryngoscopy and a bougie for tracheal intubation can increase success rates in a HEMS setting. Previous literature includes case series of the use of this method for patients with difficult airway . Traditionally, both devices are used separately and generally only in the case of a difficult airway.…”
Section: Discussionmentioning
confidence: 99%
“…A bougie is usually used only with direct laryngoscopy. Case reports describe use of a bougie and videolaryngoscopy in cases of difficult airway producing good results .…”
Section: Introductionmentioning
confidence: 99%
“…This is in particular true in patients with distorted anatomy where there is little room for manipulation. 8 This problem can be overcome by using an adjunct, for example, Frova introducer, as described by Vinayagam et al 9 I have also described the use of a fiber-optic scope as a “smart stylet” technique. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Применение видеоларингоскопов со специаль ными клинками для трудной ИТ улучшает визуализацию гортани, повышает вероятность успешной ИТ и может быть рекомендовано в качестве альтернативной методики или техники первого выбора при прогнозируемой трудной ИТ и наличии устройства [76,77]. Рекомендуется придание дистальному концу ЭТТ формы «хоккейной клюшки».…”
Section: уровень убедительности рекомендаций -Iia (уровень достоверноunclassified